Frequency, characteristics, and immunological accompaniments of ataxia in anti-NMDAR antibody-associated encephalitis - Jesse, Sarah; Riemann, Marie; Schneider, Hauke; Ringelstein, Marius; Melzer, Nico; Vogel, Niklas; Pfeffer, Lena Kristina; Friese, Manuel A.; Sühs, Kurt-Wolfram; Hudasch, Dominica; Schwenkenbecher, Philipp; Günther, Albrecht; et al. (Frontiers in Immunology, 2024)
IntroductionVery rarely, adult NMDAR antibody-associated encephalitis (NMDAR-E) leads to persistent cerebellar atrophy and ataxia. Transient cerebellar ataxia is common in pediatric NMDAR-E. Immune-mediated cerebellar ataxia may be associated with myelin oligodendrocyte glycoprotein (MOG), aquaporin-4 (AQP-4), kelch-like family member 11 (KLHL11), and glutamate kainate receptor subunit 2 (GluK2) antibodies, all of which may co-occur in NMDAR-E. Here, we aimed to investigate the frequency, long-term outcome, and immunological concomitants of ataxia in NMDAR-E.MethodsIn this observational study, patients with definite NMDAR-E with a follow-up of >12 months were recruited from the GENERATE registry. Cases with documented ataxia were analyzed in detail.ResultsIn 12 of 62 patients (19%), ataxia was documented. Bilateral cerebellar ataxia without additional focal CNS findings was found in four (one child and three adults); one of these was previously reported as a case with persistent cerebellar atrophy and ataxia. Two patients with bilateral cerebellar ataxia had additional focal neurological symptoms, optic neuritis and facial palsy. Two patients developed hemiataxia: one with diplopia suggesting brainstem dysfunction and the other probably resulting from cerebellar diaschisis due to contralateral status epilepticus. In all but the one developing cerebellar atrophy, cerebellar ataxia was transient and not associated with a worse long-term outcome. In all five patients with cerebellar ataxia tested, MOG, AQP-4, GluK2, and KLHL11 antibodies were negative. In two additional patients negative for both MOG and AQP-4 antibodies, ataxia was sensory and explained by cervical myelitis as part of multiple sclerosis (MS) manifesting temporal relation to NMDAR-E. One of the patients with bilateral ataxia with focal neurological deficits was also diagnosed with MS upon follow-up. Finally, in two patients, ataxia was explained by cerebral hypoxic damage following circulatory failure during an ICU stay with severe NMDAR-E.DiscussionAtaxia of different types is quite common in NMDAR-E. Cerebellar ataxia in NMDAR-E is mostly transient. NMDAR-E followed by persistent ataxia and cerebellar atrophy is very rare. Cerebellar ataxia in NMDAR-E may not be explained by concomitant KLHL11, MOG, AQP-4, or GluK2 autoimmunity. Of note, ataxia in NMDAR-E may result from treatment complications and, most interestingly, from MS manifesting in temporal association with NMDAR-E.